Investigation of a Combined Hydrogen and Oxygen Spillover Mechanism for Syngas Electro-Oxidation on Ni/YSZ. Issue 2 (6th December 2016) - Ong, K.; Hanna, J.; Ghoniem, A. F.
Abstract : An accurate, comprehensive model for the individual and simultaneous electro-oxidation of H2 and CO on Ni-YSZ is necessary to predict SOFC performance for a range of gaseous fuels. A mechanism that combines hydrogen (H) spillover to YSZ with oxygen (O) spillover to nickel is implemented in a previously-validated 1D-MEA model with detailed gas-phase transport and surface reforming kinetics in the anode. This model is then successfully fitted to a wide range of experimental polarization data for fuel mixtures. The H and O spillover pathways are then investigated in depth for two anode fuel mixtures: 20% H2 + 80% N2 and 20% H2 + 80% CO. Although these studies confirm that H spillover is typically the dominant source of current, they also show that the current produced by O spillover is non-negligible at higher currents. Furthermore, it is observed that H2 adsorption to nickel becomes the rate-limiting step at high currents in the hydrogen pathways, while the current produced by O spillover to CO ( Ni ) is never limited by the rate of CO adsorption. The model is then successfully compared to two independent lower temperature data sets. Together these results demonstrate that it is important to model both spillover pathways on Ni/YSZ and to account for rate-limiting H2 adsorption at high currents.